Kajian potensi sistem maklumat geografi sebagai mekanisma memantapkan pengajaran dan pembelajaran (P&P) Geografi di sekolah menengah rendah / Zakaria Mat Arof, Ashraf Abdullah and Rosmadi Fauzi - Mat Arof, Zakaria; Abdullah, Ashraf; Fauzi, Rosmadi (Universiti Teknologi MARA, Perlis, 2014)
Geography is a field of study related to the earth and its features. School teachers have to use their own creativity to clarify and explain the elements of space which is complex using a conventional means. The skill is much-needed in analyzing these elements as they are the foundation for decision-making. The constraint is in providing a good mechanism to process those semi-structure data, which have resulted in lacking of teaching and learning Geography in school. The development of technology especially ICT (Information, Communication and Technology) has opened a new chapter in geographical knowledge exploration and enables better control. This paper displayed a merge of the technology and GIS (Geography Information System) in developing a support mechanism namely Smart_Geog for teaching and learning of geography in schools. GIS is the only computerized information management system that allows geographic data to be collected, processed and manipulated to enhance geographical knowledge. The Smart_Geog design conceptual is highlighted and its application is also discussed. Majority of the respondents from the focus group had agreed with the suggestions. It is expected that Smart_Geog will create new momentum to manage a dynamic spatial data and efficiently enhance the teaching and learning of Geography in Malaysian schools.